Fertility preservation in a young female with rectal mucinous adenocarcinoma and tailgut cyst: a multidisciplinary case report - Mustafa, Muhammad; Asim, Wajiha; Memon, Kanwal J.; Aamir, Muhammad Shafay; Rirzvi, Ali Raamiz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Colorectal cancer (CRC) in women of reproductive age is rare, and its coexistence with congenital lesions such as tailgut cysts is exceptionally uncommon. Moreover, fertility preservation during multimodal oncologic therapy remains an evolving domain in young rectal cancer patients. We report a 22-year-old female, gravida 2 para 1, who presented with altered bowel habits. Imaging revealed an irregular rectal mass with posterior fat plane loss and a presacral cystic lesion suggestive of a tailgut cyst. Biopsy confirmed moderately differentiated mucinous adenocarcinoma of the rectum. Given the need for pelvic radiotherapy, ovarian transposition was performed to preserve fertility. The patient subsequently received 28 sessions of radiotherapy followed by six cycles of neoadjuvant CAPOX chemotherapy (capecitabine and oxaliplatin). Abdominoperineal resection was later performed, during which the presacral lesion was excised and confirmed histologically as a benign tailgut cyst. Post-treatment monitoring showed normalization of carcinoembryonic antigen (CEA) levels and no evidence of recurrence. This case highlights the importance of a multidisciplinary approach incorporating early diagnosis, fertility-preserving surgical strategies, and contemporary chemoradiation protocols. While ovarian transposition demonstrated preserved ovarian function, long-term follow-up remains crucial. The coexistence of a tailgut cyst and rectal adenocarcinoma in such a young patient raises potential embryological and oncogenic associations that merit further investigation. Fertility preservation should be an integral component of CRC management in young women. This case underscores the feasibility of successful oncologic and reproductive outcomes through personalized, multidisciplinary care.